Propuesta metodológica para la elaboración de un plan estratégico de gestión de activos sector eléctrico (2018)
An adequate and correct review of the literature about asset management in the electricity sector serves as a point of reference for the development of tools that in the future strengthen the implementation of asset management systems in the sector, and it also allows presenting the different methodologies used in companies with satisfactory and documented experiences.In order to verify the current status of asset management in the electricity sector and detect the best practices adopted by companies in the construction of the Asset Management Strategic Plan, the present document was developed with the purpose of giving guidelines to those companies in the sector, which are interested in creating their own asset management system.The work begins with the presentation of a historical reference framework of the Asset Management System, subsequently, it is presented a series of companies which already have an asset management system implemented and in some cases certified, which have already gone through the initial stage of the implementation of the Asset Management System and have in their web pages documented all this process, therefore, the previous procedure allowed us to gather all this information, to study, analyze and classify it. Based on these results, a methodology for the preparation of the Asset Management Strategic Plan is proposed, in the end the methodology is developed through an example and it is closed with the presentation of conclusions and obtained results.